Note from the Editor-in-Chief - Sivakumaran, Nikita (Consilience, 2016)
Dear readers, It is with great pleasure that I announce the publication of Issue XVI of Consilience: The Journal of Sustainable Development. In a time of great political turbulence, the importance of maintaining pluralistic debate increases and is further needed as an instrument of democracy and progress. With large-scale immigration escalated by war, conflict, and persecution, many countries will need to anticipate how to cope with fluctuating populations—not only in terms of the economic impact of such sudden migration but also the environmental consequences. The recent Brexit referendum introduces another element of uncertainty into both migration patterns in the European region and into the future of environmental quality controls and legislation in the UK. Given these recent events, the editing team atConsilience has curated a selection of papers for this issue that discuss sustainability in population-dense contexts that we hope will prove useful for future discourse. Our mission remains to promote dialogue and understanding of issues in sustainable development that affect not only individual communities, but the greater collective well-being of our planet. Our authors have worked diligently to provide innovative perspectives to perpetual challenges in sustainable development. We invite you to think critically about their arguments, further our understanding of their claims, and challenge their assumptions. Through interaction between practitioners, scholars, and researchers, we hope the ensuing dialogue will offer fruitful solutions to the most pressing challenges facing our planet. As always, we welcome constructive feedback and hope that our work inspires you to engage with the issues. If you have any questions, comments, or concerns, please do not hesitate to contact us at contact@consiliencejournal.org. Regards, Nikita Sivakumaran Editor-in-Chief